PENGARUH LINGKUNGAN KERJA, BEBAN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI BNN JAKARTA TIMUR SELAMA PANDEMI COVID-19 - Daniel Hamonangan, (2021)
This study is a quantitative study that aims to determine the effect of the work environment, workload, and organizational culture on East Jakarta BNN employees during the COVID-19 pandemic. This study uses a sample size of 35 respondents, which are all employees of the East Jakarta BNN. The analysis technique in this study is to use the Coefficient of Determination Test, T test (partial), and F test (simultaneous) using SmartPLS 3.0 software. The test results show that (1) work environment has an effect but not significant on East Jakarta BNN employees, (2) workload has a significant effect on East Jakarta BNN employees, (3) organizational culture has a significant effect on East Jakarta BNN employees, and (4) work environment, workload, and organizational culture have a significant joint effect on East Jakarta BNN employees during the COVID-19 pandemic.